INTEGRATED ENTERPRISE RISK MANAGEMENT IN DIGITAL AND POST PANDEMIC COVID–19 ERA: LEVERAGING ON BUSINESS MODEL CANVAS FOR THE FUTURE OF MALAYSIAN ARMED FORCES - ASMUNI, MUHAMMAD HARIS; AHMAD DAHLAN, ABDUL RAHMAN (Journal of Information Systems and Digital Technologies, 2023)
As stated in the Defence White Paper, Malaysia has planned to construct Malaysian Armed Forces (MAF) of the future, which will have five key thrusts: jointness, interoperability, technology driven, ability to operate in two theatres simultaneously, and mission oriented. It literally refers to Malaysia's status as a maritime nation and the government's dedication to the three pillars of the country's defence strategy: concentric deterrence, comprehensive defence, and credible cooperation. In addition, the report emphasised the importance of focusing on non-traditional security challenges such as terrorism, piracy, and marine security, as well as applying Industrial Revolution 4.0 (IR 4.0) technology to strengthen defence. The current state of digital transformation in the post-COVID-19 period has a significant impact on achieving the MAF's vision that has been outlined in the Defence White Paper. MAF's management should be in sync with the organization's strategic goals. To guarantee that the vision is realised, potential risks should be recognised, mitigated, reduced and/or eliminated. Integrated enterprise risk management (IERM) is a critical component of organisation‘s success, by assuring force preparedness in the face of any threats and challenges. This paper offers a possible IERM Business Model, using Business Model Canvas (BMC) framework, for MAF to consider, deliberate and adapt. The proposed MAF IERM business model is compliant with MS ISO 31000:2018 and ISO 27000 Information Security Management System (ISMS) in risk assessment, and as part of the digital transformation effort.